2007
DOI: 10.1073/pnas.0707909104
|View full text |Cite
|
Sign up to set email alerts
|

Maternal heparin-binding-EGF deficiency limits pregnancy success in mice

Abstract: An intimate discourse between the blastocyst and uterus is essential for successful implantation. However, the molecular basis of this interaction is not clearly understood. Exploiting genomic Hbegf mutant mice, we show here that maternal deficiency of heparin-binding EGF-like growth factor (HB-EGF) defers on-time implantation, leading to compromised pregnancy outcome. We also demonstrate that amphiregulin, but not epiregulin, partially compensates for the loss of HB-EGF during implantation. In search of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 44 publications
1
112
0
Order By: Relevance
“…Several tens of genes were up‐regulated 2 h after the T13 injection (Table 1). Among the genes, we focused on Hbegf and Ptgs2 (encoding COX‐2), because they are responsible for decidualization and knockout of these genes interfered with implantation (Lim et al , 1997; Song et al , 2002; Wang et al , 2004; Xie et al , 2007; Large et al , 2014), as was observed in Lpar3 KO mice (Ye et al , 2005). Both Hbegf and Ptgs2 were transiently induced, peaking at 2–9 h after the T13 injection (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several tens of genes were up‐regulated 2 h after the T13 injection (Table 1). Among the genes, we focused on Hbegf and Ptgs2 (encoding COX‐2), because they are responsible for decidualization and knockout of these genes interfered with implantation (Lim et al , 1997; Song et al , 2002; Wang et al , 2004; Xie et al , 2007; Large et al , 2014), as was observed in Lpar3 KO mice (Ye et al , 2005). Both Hbegf and Ptgs2 were transiently induced, peaking at 2–9 h after the T13 injection (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Maternal factors such as heparin‐binding epidermal growth factor (HB‐EGF) and cyclooxygenase‐2 (COX‐2) are induced in the epithelium surrounding the embryos (embryo‐epithelial interaction) and then act on the stroma to induce the expression of bone morphogenic protein 2 (Bmp2) and wingless‐related MMTV integration site 4 (Wnt4) in stroma (epithelial–stromal interaction; Lim et al , 1997; Paria et al , 2001; Song et al , 2002; Wang et al , 2004; Xie et al , 2007; Large et al , 2014). Mice in which these maternal factors (HB‐EGF, COX‐2, Bmp2, and Wnt4) are knocked out showed obvious defects in decidual reactions (Lim et al , 1997; Wang et al , 2004; Lee et al , 2007; Xie et al , 2007; Franco et al , 2011; Li et al , 2013; Large et al , 2014). Based on these observations, it has been proposed that some factor(s) are present in the embryo‐epithelial boundary and induce the expression of HB‐EGF and COX‐2 in the epithelium, which in turn facilitate the following decidual reactions through up‐regulation of Bmp2 and Wnt4 (Paria et al , 2001; Cha et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal deficiency of HB-EGF displays a compromised pregnancy outcome. 25 Beads carrying HB-EGF were very potent in inducing decidualization and stromal cell polyploidy. 26 We wonder whether HB-EGF is the key intermediary between progesterone and E2F8.…”
Section: Progesterone Activates the Expression Of E2f8 Through Hb-egfmentioning
confidence: 99%
“…Since HB-EGF has been shown to be regulated by progesterone during decidualization and tightly related to the polyploidization of decidual cells, 25,26 we assumed that HB-EGF may be involved in mediating the regulation of E2F8 expression in mouse uterus during decidualization. Compared with control group, the stromal cells treated with HB-EGF showed an increased proportion of tetraploid (Fig.…”
Section: Hb-egf/egfr/erk/stat3 Signal Pathway Regulates E2f8 Expressimentioning
confidence: 99%
“…Paria et al (2001) suggested a more defined role for HB-EGF during implantation, based upon the fact that when transferred to pseudo-pregnant mice, HB-EGF-soaked beads induced implantation-like responses, including the expression of HB-EGF on the luminal epithelium, increased vascular permeability, decidualization, and the expression of a variety of implantation markers. However, blastocysts that were devoid of the HB-EGF gene successfully implanted on the uteri of wild-type mice, calling into question the necessity for HB-EGF expression on the blastocyst surface (Xie et al, 2007). Further investigations are required to elucidate the specific role of HB-EGF expression and binding with regards to implantation.…”
Section: Growth Factorsmentioning
confidence: 99%